2012
DOI: 10.1371/journal.pone.0043022
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokine Regulation of P-glycoprotein in the Developing Blood-Brain Barrier

Abstract: Placental P-glycoprotein (P-gp) acts to protect the developing fetus from exogenous compounds. This protection declines with advancing gestation leaving the fetus and fetal brain vulnerable to these compounds and potential teratogens in maternal circulation. This vulnerability may be more pronounced in pregnancies complicated by infection, which is common during pregnancy. Pro-inflammatory cytokines (released during infection) have been shown to be potent inhibitors of P-gp, but nothing is known regarding thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 73 publications
8
58
2
Order By: Relevance
“…Indirect actions would likely be mediated by induction of pro-inflammatory cytokines. Indeed, pro-inflammatory cytokines such as IL-6 can reduce P-gp activity in the developing BBB [17]. IL-6 had the most potent effect inhibiting P-gp activity in BECs when compared to other pro-inflammatory cytokines [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect actions would likely be mediated by induction of pro-inflammatory cytokines. Indeed, pro-inflammatory cytokines such as IL-6 can reduce P-gp activity in the developing BBB [17]. IL-6 had the most potent effect inhibiting P-gp activity in BECs when compared to other pro-inflammatory cytokines [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pro-inflammatory cytokines such as IL-6 can reduce P-gp activity in the developing BBB [17]. IL-6 had the most potent effect inhibiting P-gp activity in BECs when compared to other pro-inflammatory cytokines [17]. Importantly, increased maternal levels of IL-6 temporally matched the decline in P-gp function at the developing BBB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that increase in chemokines in humans may increase the MDR1 expression in BBB endothelial cells through different signaling pathways, mainly the protein kinase-C (PKC) pathway [6], [29]. However, recent studies on rat brain capillaries indicated that there is a network of signaling mechanisms that modulate MDR1 activity involving TNF-α and IL-6 [29], [30]. On the other hand, HIV-1 Tat protein was also found to play an important role in overexpressing MDR1 in rodent BBB by activating NF-κB [31].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that treatment of the brain endothelial cell derived from various stages of development of the guinea pig with the pro-inflammatory cytokines, IL-1β, IL-6 and TNF-α has a different effect on expression of P-gp. At late gestational stage and at postnatal stage, IL-1β, IL-6 and TNF-α exposure resulted in a dose-dependent decrease in P-gp function (Iqbal et al, 2012). Cytokine-induced reductions in P-gp function were associated with decreased ABCB1 mRNA expression (Iqbal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%